Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1121/1.1882945
|View full text |Cite
|
Sign up to set email alerts
|

Echolocation signals of the free-ranging Yangtze finless porpoise (Neophocaena phocaenoides asiaeorientialis)

Abstract: The goals of this study were to compare the serum chemistry and hematology values of wild and semi-natural free-ranging Yangtze Finless Porpoises (Neophocaena asiaeorientalis ssp. asiaeorientalis) populations and to ascertain how these values change with the different environmental condition. For this study, samples were collected from 81 YFPs, 35 living in the wild and 46 living in a semi-natural reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 13 publications
2
52
0
Order By: Relevance
“…Odontocetes, specifically, have evolved the use of echolocation, in which a sound is produced by the whale and then that whale listens for a returning echo bouncing off of a target. Echolocation type signals have been reported in over 70 studies in a variety of odontocete species, indicating that the entire clade utilizes echolocation (e.g., review in Au, 1993;Miller et al, 1995;Johnson et al, 2004;Li et al, 2005;Madsen et al, 2005a,b). Evidence for echolocation in dolphins was described early, but not until a study by Norris et al (1961) was the discrimination ability of dolphins using echolocation demonstrated.…”
Section: Echolocation and Sound Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Odontocetes, specifically, have evolved the use of echolocation, in which a sound is produced by the whale and then that whale listens for a returning echo bouncing off of a target. Echolocation type signals have been reported in over 70 studies in a variety of odontocete species, indicating that the entire clade utilizes echolocation (e.g., review in Au, 1993;Miller et al, 1995;Johnson et al, 2004;Li et al, 2005;Madsen et al, 2005a,b). Evidence for echolocation in dolphins was described early, but not until a study by Norris et al (1961) was the discrimination ability of dolphins using echolocation demonstrated.…”
Section: Echolocation and Sound Sourcesmentioning
confidence: 99%
“…Norris, 1961;review in Au, 1993;Miller et al, 1995;Johnson et al, 2004;Li et al, 2005;Madsen et al, 2005a,b), suggesting that the entire lineage utilizes echolocation. During echolocation, the animal produces a sound and then listens for a returning echo from the target.…”
Section: Introductionmentioning
confidence: 99%
“…The porpoise's frequency-dependent general regions of low and high frequency sensitivity are less specific than in the bottlenose dolphin, which shows considerable (near 40 dB) differences across the head (Møhl et al, 1999). A double-acoustic window is intriguing for porpoises as they are considered to mainly produce high frequency echolocation sounds Li et al, 2005), which would be heard best from the front. Dolphins, in contrast, produce a range of sounds including lower frequency whistles and hear lower frequencies well from the side, presumably for evaluating whistle directionality (Lammers and Au, 2003;Popov et al, 2008).…”
Section: Relative Hearingmentioning
confidence: 99%
“…¼ 6.92), and pulse durations ranging from 30 to 122 ls with an average of 68 ls (S.D. ¼ 14.12) (Li et al, 2005a). These narrow-band ultrasonic pulses are quite different from background noise and other artificial sources, and therefore can be easily detected acoustically.…”
Section: Introductionmentioning
confidence: 99%